Density but not climate affects the population growth rate of guanacos (Lama guanicoe) (Artiodactyla, Camelidae) - Zubillaga, María (2014)
We analyzed the effects of population density and climatic variables on the rate of population growth in the guanaco (Lama guanicoe), a wild camelid species in South America. We used a time series of 36 years (1977-2012) of population sampling in Tierra del Fuego, Chile. Individuals were grouped in three age-classes: newborns, juveniles, and adults; for each year a female population transition matrix was constructed, and the population growth rate (Λ) was estimated for each year as the matrix highest positive eigenvalue. We applied a regression analysis with finite population growth rate (Λ) as dependent variable, and total guanaco population, sheep population, annual mean precipitation, and winter mean temperature as independent variables, with and without time lags. The effect of population size was statistically significant, but the effects of the sheep population and the climatic variables on guanaco population growth rate were not statistically significant.